Problematics of Granting Dispensation for Marriage that Leads to Child Divorce Study at Pasuruan Class 1A Religious Court - Mukti, Tantri Hari (Islamic Circle, 2025)
The granting of marriage dispensation to minors is an increasingly widespread phenomenon in Indonesia even though the minimum age of marriage has been raised through the revision of the Marriage Law. This study aims to analyse the problematics of granting marriage dispensation and its implications for the high rate of child divorce. Through a qualitative approach with case studies and analysis of data from the Pasuruan Religious Court and related agencies, this study found that many marriage dispensations were granted due to cultural factors, pregnancy outside marriage, and family pressure. However, the emotional, economic and social unpreparedness of young couples proved to be the main factor triggering divorce at a young age. These findings suggest that the process of granting marriage dispensation tends to be a mere formality without considering the psychological readiness of the prospective bride and groom. Therefore, there is a need to evaluate the marriage dispensation policy and strengthen premarital education and child protection to prevent the long-term impact of child divorce.